Phase-amplitude coupling of delta brush unveiling neuronal modulation development in the neonatal brain - Shibata, Takashi; Otsubo, Hiroshi (Neuroscience letters, 2020)
•Phase-amplitude coupling identified delta brushes as complex waveforms of slow delta waves and alpha-beta activities.•Phase-amplitude coupling of delta brushes being maximum around 32–36 post-menstrual weeks with occipital predominance.•Delta brushes have consistent coupling phases 0° or 180° between slow waves and alpha-beta activities through 31–40 weeks.•Phase-amplitude coupling might reflect the cortical neuronal fast activity modulated by slow waves of subcortical regions. Delta brushes are an indicator of brain maturity on a neonatal EEG. We investigated phase-amplitude coupling (PAC) between slow delta waves and superimposed alpha–beta activity in delta brushes to elucidate the spatiotemporal developments of the delta brush with post-menstrual weeks (PMW). The subjects were 18 neurologically intact patients (seven girls). We analyzed EEG within 42 PMW. Patients were divided into four age groups as follows: PMW ≤30w; 31–34 w; 35–38 w; and 39–42 w. We selected up to three epochs of 2-minute EEG segments including delta brushes. We calculated the modulation index (MI), direct mean vector length (dMVL), and mean of phase angle of coupling by PAC between slow waves (0.5–1.5 Hz) and fast activities (8–25 Hz) in four regions (F: Fp1 and Fp2, C: C3 and C4, T: T3 and T4, O: O1 and O2). We collected data from 18 patients and 31 epochs between 29 and 42 PMW, which comprised one, four, five, and eight patients, and two, seven, eight, and 14 epochs in the ≤30w, 31–34 w, 35–38 w, and 39–42 w groups, respectively. There were significant differences in the dMVL between the four regions in age groups ≤30w (P =  0.033) and 31–34w (0.017). Both MI and dMVL showed that delta brushes became higher in the occipital region from 32 to 36 PMW. The mean phase angle of coupling concentrated around either 0° or 180° for all age groups. PAC analysis revealed the spatiotemporal relations of alpha–beta activities that are modulated by slow delta waves in neonatal delta brushes. The delta brushes appeared to be at a maximum around 32–36 PMW with the predominant occipital distribution. The PAC of the delta brush might represent the cortical neuronal fast activity that is modulated by slow delta waves of subcortical regions during a particular neonatal period.